2000
DOI: 10.1086/309222
|View full text |Cite
|
Sign up to set email alerts
|

The 1 Micron FeiiLines of the Seyfert Galaxy I Zw 1

Abstract: Infrared spectrophotometric observations from 0.8 to 2.5 km are presented for the narrow-line, type 1 Seyfert galaxy I Zw 1. The data clearly reveal Fe II j9997, j10501, j10863, and j11126Èthe so-called "" 1 km Fe II lines.ÏÏ These features are by far the strongest Fe II transitions in the entire 0.8È2.5 km spectral region and, relative to the hydrogen lines, are equal or stronger in I Zw 1 than in any of the Galactic sources in which they have been detected previously. The 1 km Fe II lines, which share a comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 39 publications
4
62
0
Order By: Relevance
“…Collin & Joly 2000). Observationally, these lines have been previously detected in only six extragalactic objects, all NLSy1s: I Zwicky 1 (Rudy et al 2000), Mrk 478 (Rudy et al 2001), 1H 1934, Ark 564, Mrk 335, and Mrk 1044(Rodríguez-Ardila et al 2002. Detailed discussions on the origin of the lines can be found in these papers.…”
Section: Resultsmentioning
confidence: 92%
“…Collin & Joly 2000). Observationally, these lines have been previously detected in only six extragalactic objects, all NLSy1s: I Zwicky 1 (Rudy et al 2000), Mrk 478 (Rudy et al 2001), 1H 1934, Ark 564, Mrk 335, and Mrk 1044(Rodríguez-Ardila et al 2002. Detailed discussions on the origin of the lines can be found in these papers.…”
Section: Resultsmentioning
confidence: 92%
“…This reddening is that inferred from the COBE IR maps and is as given in NASA's Extragalactic Database ( NED). There may be other internal extinction intrinsic to I Zw 1 (see also Laor et al 1997;Rudy et al 2000). We discuss further the limits on any intrinsic dust in I Zw 1 in x 4.5.…”
Section: Dereddening the Spectrum Correcting For Galactic Extinctionmentioning
confidence: 88%
“…Our BLR fit to the Fe ii 2100Y 3050 8 emission does not require any intrinsic extinction due to dust. It must be mentioned that Rudy et al (2000), based on the observed intensities of O i k1304 and O i k8446, deduce an additional reddening of E(B À V ) ¼ 0:13 beyond that necessary from Galactic extinction. This assumes a Savage & Mathis (1979) extinction law.…”
Section: Lower Density Component As Revealed Through the Fe II Emissionmentioning
confidence: 99%
“…The ultraviolet spectra of active galactic nuclei (AGNs) with broad-line regions (BLRs) exhibit a quasi-continuum of thousands of blended iron emission lines, dominated by Fe ii (Wills et al 1980a(Wills et al , 1980b; numerous Fe ii transitions are also present in the optical (Boroson & Green 1992;Véron-Cetty et al 2004) and near-infrared (Rudy et al 2000(Rudy et al , 2001Rodríguez-Ardila et al 2002). Since their recognition as a significant component of the BLR emission spectrum, these Fe ii transitions have been the subject of intense observational scrutiny and theoretical modeling (Netzer 1980(Netzer , 1990Kwan & Krolik 1981;Netzer & Wills 1983;Wills et al 1985;Elitzur & Netzer 1985;Collin-Souffrin et al 1986, 1988Penston 1987;Dumont & Collin-Souffrin 1990;Sigut & Pradhan 1998, 2003Verner et al 1999).…”
Section: Introductionmentioning
confidence: 99%